Oral Rehydration Therapy Utilization and Associated Factors Among Children with Diarrhea in Debre Berhan, Ethiopia, 2020 - Wubetu AD; Engda AS; Yigzaw HB; Mulu GB (Dove Medical Press, 2021)
Abate Dargie Wubetu,1 Abayneh Shewangzaw Engda,1 Hailu Belay Yigzaw,2 Getaneh Baye Mulu3 1Debre Berhan University, College of Health Science, Department of Psychiatry, Debre Berhan, Amhara, Ethiopia; 2Adigrat University, College of Health Science, Department of Psychiatry, Adigrat, Tigray, Ethiopa; 3Debre Berhan University, College of Health Science, Department of Nursing, Debre Berhan, Amhara, EthiopiaCorrespondence: Abate Dargie Wubetu Email abatedargie2001@gmial.comBackground: Oral rehydration therapy is a critical intervention to save the lives of children during episodes of diarrhea and vomiting. However, millions of children die every year due to failure to replace fluid effectively. Nearly all dehydration-related deaths can be preventable by prompt administration of rehydration therapy. The current study aimed to assess oral rehydration therapy utilization and associated factors among children with diarrhea in Debre Berhan town.Methods: Community-based cross-sectional study was conducted from February to March 2020. The study participants were selected by systematic random sampling. The first household was selected randomly by the lottery method. The collected data were checked for completeness and relevance, and then entered into EPI data and transferred to SPSS for analysis. Multivariate logistic regression was used to determine the ORT utilization and predictor variables. A p-value less than 0.05 was considered a cutoff point for statistical significance for all statistical tests.Results: The study included 233 participants with a 99% response rate. Among them, 73% [95% Cl: 66.8 78.6] of caregivers had given oral rehydration therapy to their children. Previous use of oral rehydration therapy [AOR: 5.3, Cl: 2.1– 13.32], health-seeking behavior [AOR: 5.7, Cl: 2.07– 15.6], knowledge about oral rehydration therapy [AOR: 4.2, Cl: 1.7– 10.46], caregivers’ perception of tooth eruption [AOR: 3.13, Cl: 1.08– 9], weaning as causes of diarrhea [AOR: 6.7, Cl: 2.49– 17.9], and recognize the severity sign of dehydration [AOR: 5.6, Cl: 2.16– 14.7] became significant factors of oral rehydration therapy.Conclusion: Nearly two-thirds of the mothers give oral rehydration therapy while their child develops diarrhea. Mothers had previous oral rehydration therapy, good health-seeking behavior, knowledge about oral rehydration therapy, caregivers’ perception of tooth eruption, and weaning as causes of diarrhea. Signs to recognize the severity of dehydration were important factors with oral rehydration therapy utilization. It will be better to give mothers special attention to hindering factors from giving oral rehydration therapy for their beloved child during diarrheal disease.Keywords: ORT, children, associated factors, Amhara, North Shoa, Ethiopia